2008
DOI: 10.1016/j.bpc.2007.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the stochastic nature of intracellular calcium oscillations from experimental data

Abstract: Calcium has been established as a key messenger in both intra-and intercellular signaling. Experimentally observed intracellular calcium responses to different agonists show a variety of behaviors from simple spiking to complex oscillatory regimes. Here we study typical experimental traces of calcium oscillations in hepatocytes obtained in response to phenylephrine and ATP. The traces were analyzed with methods of nonlinear time series analysis in order to determine the stochastic/deterministic nature of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 55 publications
4
50
0
Order By: Relevance
“…Single hepatocytes were isolated from 150 -250 g of female Wistar rats by collagenase digestion as described previously (62,63).…”
Section: Isolation Of Hepatocytesmentioning
confidence: 99%
“…Single hepatocytes were isolated from 150 -250 g of female Wistar rats by collagenase digestion as described previously (62,63).…”
Section: Isolation Of Hepatocytesmentioning
confidence: 99%
“…Mathematically, a linear system of inequalities and equations can be solved by the Simplex method even when containing many unknowns. By this method we find a set of solutions to (8) and (9). It is…”
Section: Applicationsmentioning
confidence: 99%
“…Transfer of IP 3 across gap-junctions (connexins) may also contribute for the calcium elevation [4], though in a minor degree [2,5,6]. Other recent studies have shown that intracellular Ca 2+ oscillations are basically a form of correlated noise [7], which raises the question of stochasticity and reproducibility of the signal propagation and the corresponding network. While questions concerning the details of the propagating mechanisms remain an important matter of discussion [8], we are here interested in extracting insight from the inter-connectivity between cells by keeping track of Ca 2+ signals.…”
Section: Introductionmentioning
confidence: 99%